Experimental determination of the molecular weight of some binary mixtures and petroleum liquids (2013)
Accurate molecular weights of pure compounds are available and can be readily obtained in the literature. However, those of binary and multi-component mixtures are not readily available and are usually obtained from pure components by applying mixing rules, which may not be very accurate. The molecular weights of n-Nonane+n-Tetradecane. n-Hexane+n-Nonane. n-Hexane+Toluene. Toluene+n-Tetradecane and some petroleum liquids were experimental I: determined using a cryoscope. The results were compared with estimates from Kay's mixing rule and the observed deviations used to modify Kay's equation in order to obtain an improved mixing rule for the molecular weight of binary mixtures. A simple relation was also established for predicting molecular weight of petroleum liquids from API gravity. The average absolute deviation (AAD) of 0.04 and 0.40 for the molecular weight of heavy and light petroleum liquids respectively represents an improvement over most of the existing correlations.